Glaucoma after Penetrating Keratoplasty: Incidence, Risk Factors, and Management - Nilgun Yildirim; Huseyin Gursoy; Afsun Sahin; Ahmet Ozer; Ertugrul Colak (Journal of Ophthalmology)
Purpose. To report the incidence and risk factors for postkeratoplasty glaucoma (PKG), as well as its management. Subjects and Methods. 122 eyes, (43% with pseudophakic and aphakic bullous keratopathy (PABK)) which underwent penetrating keratoplasty (PK), were analyzed. Results. The rate of PKG development was 34% within 39 months of follow-up. PABK, corneal perforations, keratitis, and previous high intraocular pressure (PHIOP) were high risk factors for PKG. Glaucoma was controlled medically in 62% of PKG cases. Surgery (Ex-PRESS shunt in 63%) and diode laser cyclophotocoagulation were applied in others (38%). The rate of postoperative complications and graft survival was similar in eyes with and without PKG. Conclusion. PHIOP, preoperative diagnoses other than keratoconus, and corneal dystrophies were highly associated with PKG. Ex-PRESS shunts were effective in refractory PKG. If glaucoma is controlled, it is possible to obtain similar rates of graft survival and postoperative complications in eyes with and without PKG.